Prevalence and sociodemographic factors of depression, anxiety and stress in Saudi Arabia: a survey of respiratory therapists - Aldhahir, Abdulelah M. (Frontiers in Psychiatry, 2024)
Background Depression, anxiety and stress are prevalent among healthcare providers but limited data is available regarding respiratory therapists (RTs). This study aimed to assess the prevalence of depression, anxiety and stress, and identify the associated sociodemographic factors among RTs in Saudi Arabia. Methods A cross-sectional online survey was distributed to RTs in Saudi Arabia. Data were summarized using frequency and percentages. Stress, anxiety, and depression prevalence rates were expressed as proportions with 95% confidence intervals (CI). The associated factors of stress, anxiety, and depression were subjected to logistic regression. Results Overall, 988 (91%) RTs, 661 (66.9%) males, completed the online survey. The prevalence (95% CI) of depression, anxiety and stress among RTs was 81.3% (0.787, 0.837), 89.6% (0.875, 0.914), and 45.5% (0.424, 0.487), respectively. RT staff who were ≥41 years old, divorced, widowed or separated, or had > 10 years of clinical experience were more likely to experience stress. RTs who were (divorced, widowed or separated), did not live with their family, were current smokers, or worked the night shift were more likely to experience anxiety. RTs who were (divorced, widowed or separated), were current smokers, had >10 years of clinical experience were more likely to experience depression. Conclusion Stress, anxiety and depression are prevalent among RTs. Several sociodemographic factors are associated with the incidence of stress, anxiety and depression.